High-density lipoprotein particles are associated with the risk of mortality from all-causes and cardiovascular diseases (CVDs) in patients with CVD: a systematic review and meta-analysis study - Elham Sharifi-Zahabi; Nooshin Nasiri; Fatemeh Hajizadeh-Sharafabad; Sobhan Mohammadi; Shaghayegh Shahbazi; Nahid Salehi (Lipids in Health and Disease)
Abstract Background & aims Increasing data indicate that the concentration of high-density lipoprotein particles (HDL-p) may be a strong indicator of cardiovascular disease. This study aimed to carry out a meta-analysis to examine the link between subclasses of HDL-p and the hazard of mortality in individuals suffering from cardiovascular diseases (CVDs). Methods A rigorous systematic search was executed through Scopus, PubMed, and Web of Science up to April 2025. Results Seven unique cohort studies were deemed eligible for incorporation in this meta-analysis. The overall hazard was derived by applying a random effects model. The results indicated a negative association of total HDL-p (RR: 0.74, 95% CI: 0.69–0.78, P < 0.001) and small HDL-p with all-cause mortality (RR: 0.69, 95% CI: 0.63–0.75, P < 0.001) for each 5 µmol/l increment. Similarly, each 5 µmol/l large HDL-p was directly related to all-cause mortality (RR: 1.71, 95% CI: 1.14– 2.56; P = 0.009). Moreover, each 5 µmol/l increase in small HDL-p was linked to a 33% reduction in CVD mortality (RR: 0.67, 95% CI: 0.50–0.91; P = 0.01). Conclusion This study revealed that small and total HDL-p were negatively correlated with all-cause mortality, whereas latge HDL-p was positively related to mortality from all causes. Additionally, small HDL-p had an inverse relationship with CVD mortality in patients with CVD.